Isolation and Characterization of Cervical Cancer-Associated Mesenchymal Stem Cells From Primary Tumors Using Explant Culture - Surbhi Singla; Sanchita Khurana; Rashmi Bagga; Radhika Srinivasan; Shalmoli Bhattacharyya (Bio-Protocol)
Cancer-associated mesenchymal stem cells (Ca-MSCs), an integral part of the tumor microenvironment, play a major role in modulating tumor progression; they have been reported to progress as well as inhibit various cancers, including cervical cancer. To understand the exact role of Ca-MSCs in tumor modulation, it is necessary to have an optimized protocol for Ca-MSCs isolation. This work demonstrates the isolation and expansion of a primary culture of cervical cancer–associated MSCs (CCa-MSCs) from the biopsy sample of cervical cancer patients using the explant culture technique. The isolated cells were characterized according to International Society for Cellular Therapy (ISCT) guidelines. Morphological analysis revealed that cells were adherent to the plastic surface and possessed spindle-shaped morphology. Flow cytometry analysis of the cells showed high expression (~98%) for MSC-specific cell surface markers (CD90, CD73, and CD105), negative expression (<0.5%) for endothelial cell marker (CD34) and hematopoietic cell marker (CD45), and negligible expression for HLA-DR, as recommended by ISCT. Further, trilineage differentiation potential analysis of the cells showed their osteogenic and chondrogenic potential and adipogenic differentiation. This standardized protocol will assist in the cultivation of CCa-MSCs and the study of their interactions with tumor cells and other components of the tumor microenvironment. This protocol may be utilized in the establishment of Ca-MSCs from other types of cancers as well.